Peer-to-peer file sharing over Bluetooth mobile ad hoc networks - Castro, Arvin O.
Peer-to-peer networks have been accepted and have developed to be functional on the Internet. These peer-to-peer systems created impact on how files are shared. They allowed users to share files on their network without requiring a central server to keep all the information on a single server. This attracted a number of users to share every different file types of varying sizes. Alongside that, mobile devices are also evolving. Mobile devices nowadays, have relatively large storage capacity and good processing power despite their small size. Moreover, they are now equipped with wireless communication technologies like Bluetooth, enabling them to share files wirelessly aside from ad hoc networks suitable for peer-to-peer networking. Peer-to-peer file sharing seems to be suitable for mobile ad hoc environment since mobile devices form networks arbitrarily. However, these mobile devices have limited resources posing difficulties in the implementation of a peer-to-peer network in a mobile as hoc environment. In this study, we implemented a P2P file sharing system over Bluetooth mobile ad hoc networks fit to the device limitations mentioned.